INSTRUCTOR LEADERSHIP IN EFL CLASSROOMS AND THE OUTCOMES: THE EFFECTS OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP STYLES - Erdel, Didem; Takkaç, Mehmet (TEFLIN Journal, 2020)
In this study, classroom leadership styles of English language instructors were investigated within the Full Range Leadership (FRL) framework with the purpose of determining the relationship between instructors' leadership styles and the outcomes of leader (the instructor in the classroom context) effectiveness, students' extra effort and student satisfaction. Classroom Leadership Instrument, a modified version of Multifactor Leadership Questionnaire, was administered to 300 students from English Language Teaching and English Language and Literature Departments at a Turkish state university. Research data were analyzed through inferential statistical tests and the results revealed that transformational leadership and active traits of transactional leadership significantly correlated with all three leadership outcomes. Consequently, the instructors with such leader characteristics appeared to be more effective teachers, whose students felt more satisfied with their teaching and displayed extra effort at a higher extent in the courses.